2021
DOI: 10.1152/ajplung.00578.2020
|View full text |Cite
|
Sign up to set email alerts
|

Altered lung metabolism and mitochondrial DAMPs in lung injury due to acute kidney injury

Abstract: Acute respiratory distress syndrome (ARDS) is a common cause of mortality in patients with acute kidney injury (AKI). Inflammatory crosstalk from the kidney to the lung has been shown to contribute to lung injury after AKI, but anti-inflammatory therapies have not been proven beneficial in human studies. Recently, AKI was shown to alter mitochondria and related metabolic pathways in the heart, but the impact of AKI on lung metabolism has not been investigated to our knowledge. In this study, we evaluated the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…In agreement with our work, another study demonstrated DRP1 suppresses pro-inflammatory signaling in macrophages stimulated with LPS via regulation of release of mitochondrial damage-associated molecular patterns (DAMPs) [ 33 ]. Mitochondrial DAMPs play an important role in inflammatory signaling in response to lung injury [ 53 , 54 , 55 ]. Mitochondrial DAMP release could be suppressed by DRP1-induced fission in airway epithelia following HDM exposure, though more detailed studies are needed to examine this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our work, another study demonstrated DRP1 suppresses pro-inflammatory signaling in macrophages stimulated with LPS via regulation of release of mitochondrial damage-associated molecular patterns (DAMPs) [ 33 ]. Mitochondrial DAMPs play an important role in inflammatory signaling in response to lung injury [ 53 , 54 , 55 ]. Mitochondrial DAMP release could be suppressed by DRP1-induced fission in airway epithelia following HDM exposure, though more detailed studies are needed to examine this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma mtDAMPs levels are increased after trauma [54] and sepsis [57] and the circulating concentration of mtDNA correlates with mortality in critically ill patients with ARDS [58]. We have recently shown that renal IR results in mitochondrial dysfunction in remote organs and cell types, including the lung [59]. This correlated with an increase in the mtDAMPs and mtDNA in the plasma and bronchoalveolar lavage fluid.…”
Section: Mitochondrial Functional Alterationsmentioning
confidence: 99%
“…The American Journal of Physiology -Lung Cellular and Molecular Physiology (hereafter AJP-Lung) has recently addressed inter-organ communication between the organs of the respiratory system and the liver by examining the relationship between orthotopic liver transplantation and lung injury (51). In the kidneys, which are often impacted early in patients with ARDS (52), the mechanisms of altered lung metabolism due to acute kidney injury have recently received attention in AJP-Lung (53,54). The relationship between the heart and the lungs received regular attention in the pages of AJP-Lung (55), most recently, this attention has included identifying lipid mediators of right ventricular adaptation in pulmonary hypertension (56).…”
Section: Ajp-lung Cellular and Molecular Physiologymentioning
confidence: 99%